Importance of families in care of individuals with mental disorders: nurses' attitudes - Carla Sílvia Neves da Nova Fernandes; Maria do Perpétuo Socorro de Sousa Nóbrega; Margareth Angelo; Maria Isolete Torre; Suellen Cristina da Silva Chaves (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objectives: To characterize the attitudes of nurses working in primary health care on the importance of involving families in nursing care to the person with mental disorder. Method: A cross - sectional descriptive study with a quantitative approach performed with 328 nurses who work in primary health care in Porto, Portugal. Families Importance in Nursing Care - Nurses Attitudes (FINC-NA) scale was applied. Results: Scale scores were elevated, mean value was 85.9 (Maximum possible 104). The significant correlations were with the variables: academic qualifications (p = 0.001), specialization (p = 0.002) and professional activity context (p = 0.001). Conclusion and implications for practice: Nurses demonstrate a high degree of agreement about the importance of families in nursing care to the person with mental disorder. Positive attitudes of nurses regarding the importance of involving families in care are fundamental to enhance the quality of care in the presence of mental disorder.